Nghiên cứu chế tạo vật liệu polyme compozit từ hệ nhựa epoxy/MHHPA gia cường sợi thủy tinh có mặt vi sợi xenlulo. Phần 3. Ảnh hưởng của vi sợi xenlulo hình thành do vi khuẩn đến độ bền dai phá hủy của vật liệu polyme compozit từ nhựa epoxy - Đức, Vũ Minh; Minh Ngọc, Phan Thị; Lánh, Phạm Thị; Yến Oanh, Đoàn Thị; Đô, Ngô Huy (Vietnam Journal of Chemistry, 2015)
Using bacterial cellulose as additive is the most effective means for improving performance of epoxy composites. This paper presents an experimental investigation the influence of bacterial cellulose (BC) on interlaminar fracture toughness of glass fibers reinforced epoxy composites. The interlaminar fracture toughness measured from the double cantilever beam (DCB) with 0.0 to 0.4 %BC contents. The tests showed significant improvements with 0.3 % BC contents: the fracture (GI0 and GIC-p) of ER/glass fibers/0.3 %BC increased by 128.8 % and 111.0 %, respectively in comparison with the neat epoxy composites.